In-field gait retraining and mobile monitoring to address running biomechanics associated with tibial stress fracture - Willy, R. W.; Buchenic, L.; Rogacki, K.; Ackerman, J.; Schmidt, A.; Willson, J. D. (Scandinavian Journal of Medicine & Science in Sports, 2016)
We sought to determine if an in-field gait retraining program can reduce excessive impact forces and peak hip adduction without adverse changes in knee joint work during running. Thirty healthy at-risk runners who exhibited high-impact forces were randomized to retraining [21.1 (±1.9) years, 22.1 (±10.8) km/week] or control groups [21.0 (±1.3) years, 23.2 (±8.7) km/week]. Retrainers were cued, via a wireless accelerometer, to increase preferred step rate by 7.5% during eight training sessions performed in-field. Adherence with the prescribed step rate was assessed via mobile monitoring. Three-dimensional gait analysis was performed at baseline, after retraining, and at 1-month post-retraining. Retrainers increased step rate by 8.6% (P?<?0.0001), reducing instantaneous vertical load rate (-17.9%, P = 0.003), average vertical load rate (-18.9%, P < 0.0001), peak hip adduction (2.9° ± 4.2 reduction, P = 0.005), eccentric knee joint work per stance phase (-26.9%, P < 0.0001), and per kilometer of running (-21.1%, P < 0.0001). Alterations in gait were maintained at 30 days. In the absence of any feedback, controls maintained their baseline gait parameters. The majority of retrainers were adherent with the prescribed step rate during in-field runs. Thus, in-field gait retraining, cueing a modest increase in step rate, was effective at reducing impact forces, peak hip adduction and eccentric knee joint work.